Patents, data exclusivity, and the development of new drugs - Fabian Gaessler; Stefan Wagner (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Pharmaceutical firms typically enjoy market exclusivity for new drugs from concurrent protection of the underlying invention (through patents) and the clinical trials data submitted for market approval (through data exclusivity). Patent invalidation during drug development renders data exclusivity the sole source of protection and shifts the period of market exclusivity at the project level. In instrumental variables regressions we quantify the effect of a one-year reduction in expected market exclusivity on the likelihood of drug commercialization. The effect is largely driven by patent invalidations early in the drug development process and by the responses of large originators. We hereby provide first estimates of the responsiveness of R&D investments to market exclusivity expectations.
Keywords: K41; L24; L65; O31; O32; O34; 330; patents; drugs; data exclusivity; clinical trials